The Effectiveness of HERO Training to Improve the Engagement of Disaster Volunteers - Erlyani, Neka; Zwagery, Rika Vira; Mayangsari, Marina Dwi (Interdisciplinary Social Studies, 2021)
The future development of CCeU ULM needs to consider the nature of volunteers who do not want to continue to be in the organization. Therefore, retaining volunteers to continue to be actively involved and contribute to the organization is a challenge in itself. This study aims to empirically test the "HERO" training (Hope, Efficacy, Resiliency, Optimism) to increase the engagement of disaster volunteers. The instrument used to measure psychological capital is adapted from Cetin and Basim (2012), namely Psychological Capital Scale (R= 0.941). The scale used to measure the Work Engagement of Crisis Center Unit ULM volunteers was (R= 0.935). The respondents of this study were 53 members of the ULM Crisis Center Unit, divided into men and women, with criteria for 18-25 years. This research is a quasi-experimental study with a non-randomized one-group pre-test post-test design. Statistical analysis showed 0.699 >, 0.699 < 0.05, so it can conclude that there is no significant effect of HERO training on the work engagement of CCU FK ULM members. It means that other antecedents can lead to one's work engagement.